Media framing and construction of childhood obesity: a content analysis of Swedish newspapers. (11th February 2018) - van Hooft, J.; Patterson, C.; Löf, M.; Alexandrou, C.; Hilton, S.; Nimegeer, A.
Summary: Objective: Despite lower prevalence than most European countries, childhood obesity is a Swedish public health priority due to its lasting health impacts and socioeconomic patterning. Mass media content influences public and political perceptions of health issues, and media framing of childhood obesity may influence perceptions of its solutions. This study examines framing of childhood obesity in Swedish morning and evening newspapers from 1996 to 2014. Methods: Content analysis of 726 articles about childhood obesity published in the five most‐circulated Swedish newspapers. Article content coded quantitatively and subjected to statistical analysis, describing relationships between themes and trends over time. Results: Childhood obesity was consistently problematised, primarily in health terms, and linked to socio‐economic and geographical factors. The yearly frequency of articles peaked in 2004, followed by a decline, corresponding with evidence about prevalence. Childhood obesity was framed as being driven by individual behaviours more frequently than structural or environmental factors. Structural framings increased over time, but constructions of the problem as driven by individual behaviours, particularly parenting, remained prominent. Conclusions: A relative growth in structural framings of causes and solutions over time, combined with prominent coverage of socio‐economic inequalities, might be indicative of public and political amenability towards societal‐level solutions, but individual behaviours remain prominent in framing of the issue. Health advocates might incorporate these insights into media engagement.